Association between Streptococcus mutans and Candida albicans among 3-5-year-old children with early childhood caries: A cross-sectional study - F Farhanaz; R Yashoda; M L Kalayadhav; Manjunath P Puranik (Wolters Kluwer Medknow Publications, 2017)
Introduction: Streptococcus mutans infection has been identified as an important microbial factor for early childhood caries (ECC). Candida species has been shown to enhance the adherence of S. mutans to the oral biofilm and carious tooth substance. However, there is a paucity of the literature regarding the association between S. mutans and Candida albicans related to the ECC. Aim: To assess and compare the levels of S. mutans and C. albicans among 3-5-year-old preschool children with and without ECC and to determine the association between them. Materials and Methods: A cross-sectional study was conducted among 30 children with ECC (ECC group) and 30 children without ECC (non-ECC group). Dental caries was assessed, and unstimulated saliva samples were collected. S. mutans and C. albicans counts were determined using Mutans-Sanguis agar and CHROMagar, respectively. Chi-square test and logistic regression were used. Significance levels were set at 5%. Results: There was a significant difference between ECC group and non-ECC group for S. mutans (P = 0.04) and C. albicans (P = 0.02) levels. There was no significant association between S. mutans and C. albicans in ECC and non-ECC groups. Children with ECC were more likely to have high levels of S. mutans and C. albicans when compared to non-ECC group. Conclusion: Children with ECC presented higher levels of S. mutans and C. albicans compared to children without ECC. High affinity between S. mutans and C. albicans suggests interaction between these diverse species that may mediate cariogenic development.